2011
DOI: 10.1371/journal.pone.0016878
|View full text |Cite
|
Sign up to set email alerts
|

Geographical Representativeness of Published and Ongoing Randomized Controlled Trials. The Example of: Tobacco Consumption and HIV Infection

Abstract: BackgroundThe challenge for evidence-based healthcare is to reduce mortality and the burden of diseases. This study aimed to compare where research is conducted to where research is needed for 2 public health priorities: tobacco consumption and HIV infection.MethodsWe identified randomized controlled trials (RCTs) included in Cochrane systematic reviews published between 1997 and 2007 and registered ongoing RCTs identified in January 2009 through the World Health Organization's International Clinical Trials Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…At the same time that the priorities of developed countries drives the research agenda of pharmaceutical companies, there is a disturbing underrepresentation of research addressing priority issues for developing countries [ 15 , 16 ]. Diseases of relevance to high-income countries are investigated in clinical trials seven to eight times more often than diseases whose burden lies mainly in low-income and middle-income countries [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…At the same time that the priorities of developed countries drives the research agenda of pharmaceutical companies, there is a disturbing underrepresentation of research addressing priority issues for developing countries [ 15 , 16 ]. Diseases of relevance to high-income countries are investigated in clinical trials seven to eight times more often than diseases whose burden lies mainly in low-income and middle-income countries [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization (WHO) has indicated the pressing need for a comprehensive monitoring of health research and development (R&D) to coordinate limited resources towards reducing the gaps between health research and health needs [ 1 3 ]. Mapping the global landscape of health R&D will allow for identifying diseases for which there is too much or too little research at a local level as compared to their burden at the same level [ 4 ]. The WHO is developing the Global Observatory on Health R&D and aims at analyzing multiple data sources to quantify the global state of health R&D, including clinical trial registries, publications, product pipelines, patents and grants [ 3 , 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, a recent study on tobacco use found that only 4% of randomised controlled trials included in systematic reviews and 2% of on-going trials were performed in LMICs, even though these countries represented 70% of the mortality related to tobacco use. 24 …”
Section: Discussionmentioning
confidence: 99%
“…The International Primary Care Respiratory Group (IPCRG) maintains a public website ( http://www.theipcrg.org/freshair ) to enable emerging findings to be shared widely and freely, and private pages for the logging of contextual data, as recommended in the latest guidance on implementation science reporting. 24 …”
Section: Discussionmentioning
confidence: 99%